Asuhan Keperawatan Pada Tn.T Dengan Diagnosa Acute Decompensated Heart Failure (ADHF) Di Ruang Hcu Rsud Padang Pariaman - Latifah Aini; Linda Marni; Hilma Yessi; Debby Silvia Dewi (CV. ITTC INDONESIA, 2026)
Acute Decompensated Heart Failure (ADHF) is a cardiovascular emergency characterized by an acute deterioration in heart function that requires immediate treatment. ADHF is a global health issue, with approximately 3 million cases reported annually. In Indonesia, the prevalence of heart disease is 0.85%, while in West Sumatra Province it is 0.87%. Medical record data at Padang Pariaman Regional General Hospital show an increase in ADHF cases, with 100 cases in the past year in the HCU ward. This case study aims to provide an overview of the implementation of nursing care for patients with ADHF. The method used was a case study employing a nursing process approach through observation and interviews, conducted over 5 days from February 25 to March 1, 2026, in the HCU Ward of Padang Pariaman Regional General Hospital on one patient diagnosed with ADHF. The results of the case study revealed five primary nursing problems: decreased cardiac output, ineffective airway clearance, acute pain, activity intolerance, and sleep pattern disturbance. Interventions were implemented over 5 days, focusing on cardiac care, airway management, pain management, energy management, and sleep support. Evaluation showed a gradual improvement in the patient’s condition, with sleep disturbances resolved by day 2, acute pain resolved by day 3 with a pain score of 2, airway clearance resolved by day 4, The decreased cardiac output resolved by day 5, with an oxygen saturation of 98%, and activity intolerance was partially resolved. It is hoped that the patient and family will follow the healthcare providers’ recommendations, maintain a healthy lifestyle, and attend regular follow-up visits at a healthcare facility to prevent recurrence.